Carpal tunnel relesa via limited palmar incision using rhinoplasty instruments - (:unkn) unknown (My University, 2002)
0

Objective: Carpal tunnel release via a limited palmar incision has been shown to combine the simplicity and safety of the traditional open approach with a reduction of tissue trauma and improved postoperative recovery of the endoscopie technique. A modification of this technique is presented. Methods: The operation begins with a 1.5-2 cm palmar incision, dissection is performed using a Killian periostal elevator, exposure is provided by a Killian speculum and the transverse carpal ligament is severed by angled cartilage scissors. Results: Twenty-eight carpal tunnel cases were operated using this approach without any complication. Conclusion: This technique not only pleased the surgeon by its simplicity and safety but also the patient who made a rapid and full recovery.
Keywords: Genel ve Dahili Tıp